2022
DOI: 10.7150/ijbs.69344
|View full text |Cite
|
Sign up to set email alerts
|

Over-Activation of Minichromosome Maintenance Protein 10 Promotes Genomic Instability in Early Stages of Breast Cancer

Abstract: Genomic instability is considered as one of the key hallmark during cancer development and progression. Cellular mechanisms, such as DNA replication initiation, DNA damage and repair response, apoptosis etc are observed to block progression of genomic instability and thereby induce protective effects against cancer. DNA replication initiation protein MCM10 has been previously observed to have an increased expression in different cancer subtypes. However, MCM10 association with genomic instability, cancer devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…A recent study suggests that excessive activation of MCM10 promotes genomic instability in early breast cancer 32 . Our study also found that MCM10 expression was significantly upregulated in most cancer types, which may contribute to tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggests that excessive activation of MCM10 promotes genomic instability in early breast cancer 32 . Our study also found that MCM10 expression was significantly upregulated in most cancer types, which may contribute to tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%